2012
DOI: 10.1016/j.jpain.2011.10.014
|View full text |Cite
|
Sign up to set email alerts
|

The Perception of Pain in Others: How Gender, Race, and Age Influence Pain Expectations

Abstract: Sex, race/ethnic, and age differences in pain have been reported in clinical and experimental research. Gender role expectations have partly explained the variability in sex differences in pain, and the Gender Role Expectations of Pain questionnaire (GREP) was developed to measure sex-related stereotypic attributions about pain. It is hypothesized that similar expectations exist for age and race-related pain decisions. This study investigated new measures of race/ethnic- and age-related stereotypic attribution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
159
4
24

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 233 publications
(202 citation statements)
references
References 26 publications
12
159
4
24
Order By: Relevance
“…Conversely, participants who endorsed fewer false beliefs (−1 SD) rated the black target as feeling more pain than the white target [β = −0.48, SE = 0.20, t(211) = −2.34, P = 0.020]. In other words, as in study 1, participants in study 2 who endorsed false beliefs about biological differences between blacks and whites exhibited a racial bias in pain perception similar to the bias shown in previous work (11)(12)(13)(14)(15)(16)(17). Unexpectedly, participants who did not endorse such beliefs exhibited a bias in the opposite direction.…”
Section: Studysupporting
confidence: 62%
See 1 more Smart Citation
“…Conversely, participants who endorsed fewer false beliefs (−1 SD) rated the black target as feeling more pain than the white target [β = −0.48, SE = 0.20, t(211) = −2.34, P = 0.020]. In other words, as in study 1, participants in study 2 who endorsed false beliefs about biological differences between blacks and whites exhibited a racial bias in pain perception similar to the bias shown in previous work (11)(12)(13)(14)(15)(16)(17). Unexpectedly, participants who did not endorse such beliefs exhibited a bias in the opposite direction.…”
Section: Studysupporting
confidence: 62%
“…In fact, recent work suggests that racial bias in pain treatment may stem, in part, from racial bias in perceptions of others' pain. This research has shown that people assume a priori that blacks feel less pain than do whites (11)(12)(13)(14)(15)(16)(17). In a study by Staton et al (14), for instance, patients were asked to report how much pain they were experiencing, and physicians were asked to rate how much pain they thought the patients were experiencing.…”
mentioning
confidence: 99%
“…First, our results could help health service providers to refocus their resources. For example, we found that pain, nausea and vomiting were highly undesired outcomes, hence, clinicians and healthcare professionals should dedicate some preoperative time for patient education on pain management (26)(27)(28)(29) and postoperative acute pain management. A previous study (25) had found that overall pain management systems can be improved by education on realistic pain expectations and coping strategies preoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…The role of the health care professional and diagnostic labels was described above to demonstrate how a context can influence behaviour. Wandner et al, (2012) have also reported how the perception of pain varies across gender, race and age. It seems likely that a combination of these biopsychosocial factors might (mis)inform an individual's perception and hence pain response.…”
Section: The De-conditioned Rotator Cuffmentioning
confidence: 99%